2019
DOI: 10.1186/s13048-019-0590-5
|View full text |Cite
|
Sign up to set email alerts
|

Thy-1 predicts poor prognosis and is associated with self-renewal in ovarian cancer

Abstract: BackgroundOvarian cancer is the leading cause of gynecologic cancer death in the United States despite effective first-line systemic chemotherapy. Cancer stem cells (CSCs) retain the ability to self-renew and proliferate and may be a means of harboring disease that evades standard treatment strategies. We previously performed a high-throughput screen to assess differential protein expression in ovarian CSCs compared to non-CSCs and observed that Thy-1 was more highly expressed in CSCs. Our primary aim was to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The latest findings report that in several tumors, including ovarian cancer, THY1 is overexpressed in cancer stem cells (CSC) and the tumor microenvironment, enhancing proliferation and metastasis abilities [ 7 ]. Furthermore, in HCC, THY1 expression is related to poor tumor differentiation, invasive properties, and dismal prognosis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latest findings report that in several tumors, including ovarian cancer, THY1 is overexpressed in cancer stem cells (CSC) and the tumor microenvironment, enhancing proliferation and metastasis abilities [ 7 ]. Furthermore, in HCC, THY1 expression is related to poor tumor differentiation, invasive properties, and dismal prognosis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous genes associated with stemness have been reported to be characteristic of OCSCs [ 30 , 31 ]. It was observed that 974 significantly decreased the expression of the well-known stemness genes Bmi-1, Nanog, Oct4, and Sox2 in OVCAR3 ( Figure 2 C) and OVCAR5 cells ( Figure 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…THY1 is more highly expressed in ovarian CSCs than in non-CSCs, and high THY1 expression in patients with serous OC indicates poorer outcomes. THY1 promotes proliferation and self-renewal in OC (Elizabeth et al, 2019). BGN was indicated to be an endogenous inhibitor of bladder cancer cell proliferation by antiproliferative tyrosine kinase inhibitors.…”
Section: Discussionmentioning
confidence: 99%